Penentuan Tingkat Kekumuhan Permukiman Kumuh Kota Palembang Dengan Metode Algoritma K-Means Clustering Dan Algoritma ID3 - Endah Puspita Sari; Lastri Widya Astuti; Imelda Saluza; Faradillah Faradillah; Rini Yunita (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2021)
Slum settlers are a condition of uninhabitable settlements. Slums are devided into 4 levels, namely : high slums, medium, light and not slum. To produce these four levels, method is used namely K-Means Clustering Algorithm and the ID3 Algorithm is used to give priority with pre determined attributes then accumulated with the results of clustering classified as slum level. The accuracy test is performe by using the confusion matrix method, where the data results from the K-Means Clustering method compared to the baseline data. The results obtained from the accuracy with confusion matrix is 0,70%, which means the level of truth (accuracy) between the result of the baseline data with research data is 70%.